Dynamic Characteristics Research of a Steel/CFRP Drive Shaft - Jinguang Zhang; Rui Yang; Yefa Hu; Guoping Ding; Yan Xu; Jiaying Niu (Advances in Mechanical Engineering, 2013)
The dynamic characteristics of a steel/CFRP (carbon fiber reinforced plastic) drive shaft were studied. finite element analysis (FEA) and an experiment were carried out to investigate the natural frequencies and mode shapes. The results of the experiment verified the effectiveness of the finite element model. At the same time, the FEA was used to predict the dynamic characteristics of the shaft for different stacking sequences, fiber orientation angles, and layer thicknesses. The results show that the natural frequency increases with decreasing fiber orientation angles. And the positive andnegative stacking sequences are helpful to improve natural frequency. The layer thicknesses and stacking sequences will have a pronounced effect in a specific size of the shaft.